Water Restriction on artificial inoculation for Fusarium verticillioides in corn seeds - Silva de Barros, Liliane; Carneiro Guimarães, Sebastião; Kobayasti, Leimi; Furtado de Mendonça, Elisabeth Aparecida (Scientia Plena, 2014)
Water restriction has been used in the culture media in order to inhibit or delay germination to allow for greater exposure to an inoculum, as long as the osmotic potential of the media restricts seed germination and is not detrimental to the development of pathogen colonies. To achieve the inoculation of Fusarium verticillioides in corn seeds the effects of water restriction using PDA (potato dextrose agar) + KCl and PDA + NaCl at concentration producing osmotic potentials of -0,6; -0,8; -1,0 and -1,2 MPa, on mycelial growth and conidial production of F. verticillioides, percentage of infected seeds, germination of seeds and transmission of the fungus to the corn was evaluated. There was no significant difference for conidial production of F. verticillioides and seeds germination. The PDA + KCl medium with osmotic potential between -0,6 and -1,0 MPa and PDA + NaCl with osmotic potential of -0,6 and -0,8 MPa favors the mycelial growth of F. verticillioides. The technique of using water restriction with NaCl and KCl solutes is effective in artificial inoculation of maize seeds with F. verticillioides. The PDA +NaCl and PDA + KCl medium, both in the osmotic potential of -1,2 MPa, allows 90% of transmissibility of F. verticillioides inoculated seeds to the corn stems and roots.